Image in the principal Niche on the south facing wall - Temples of India Project Team (Jio Institute, 2024)
Image in the principal niche on the south-facing wall of the Suswani Mata Temple wall is covered in drapery but based on the visible portions. It appears to be Mahishasurmardini mounted on a lion. Left upper hands of the deity are holding a shield and sword. Near the left leg is the mount Lion of the goddess.